2007
DOI: 10.1891/088667007782312122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Perpetrators, and Characteristics of Witnessing Parental Violence and Adult Dating Violence in Latina, East Asian, South Asian, and Middle Eastern Women

Abstract: The present study describes and compares the prevalence, perpetrators, and characteristics of witnessing parental violence during childhood and experiencing adult relationship violence in 251 college-educated South Asian/Middle Eastern (n = 93), East Asian (n = 72), and Latina (n = 86) women residing in the United States. Results showed that more than 50% of each ethnic group witnessed parental and adult relationship violence. For all three groups, adult psychological violence was more prevalent than physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In addition, being further along in schooling, holding traditional gender role attitudes, and higher levels of shame all predicted attitudinal acceptance of psychological aggression within a dating relationship. A separate study explored psychological aggression among married partners in Mainland China and found that about half of couples had experienced this behavior (Hou, Yu, Ting, Sze, & Fang, 2011), which is in line with estimates from other Asian countries as well (Maker & deRoon-Cassini, 2007). Taken together, these findings provide substantial evidence to hypothesize that psychological aggression is prevalent among college students in Mainland China, but it remains unexplored in the English-language literature.…”
Section: Dating Violence In Mainland Chinasupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, being further along in schooling, holding traditional gender role attitudes, and higher levels of shame all predicted attitudinal acceptance of psychological aggression within a dating relationship. A separate study explored psychological aggression among married partners in Mainland China and found that about half of couples had experienced this behavior (Hou, Yu, Ting, Sze, & Fang, 2011), which is in line with estimates from other Asian countries as well (Maker & deRoon-Cassini, 2007). Taken together, these findings provide substantial evidence to hypothesize that psychological aggression is prevalent among college students in Mainland China, but it remains unexplored in the English-language literature.…”
Section: Dating Violence In Mainland Chinasupporting
confidence: 73%
“…More than 90% of the women and more than 80% of the men in this sample had ever committed an act of psychological aggression against his or her current romantic partner. This rate is higher than what was found among married couples in Mainland China (less than 50%; Hou et al, 2011) and other Asian countries (53%-74%; Maker & deRoon-Cassini, 2007). There are a couple of possibilities for this discrepancy.…”
Section: Discussionmentioning
confidence: 61%
“…This estimate is considerably lower than other studies in South Asian women suggesting rates as high as 70 %, however, we asked only about the past 12 months and other studies asked for varying time frames [15][16][17]. Our findings, however, are quite consistent with the PRAISE study [13] which found that 16 % of women globally experienced IPV in the past year using the same definition of IPV, timeframe, and questions to assess IPV experience as the current study.…”
Section: Discussionmentioning
confidence: 92%
“…ThapaOli et al [16] found that 54 % of Nepali women living in New York had ever experienced emotional abuse and 36 % had experienced physical abuse in their lifetime. Maker et al [17] report that 70 % of women experienced abuse in her adult life but did not report separate values for Middle Eastern and South Asian populations. Ahmad et al [18] assessed South Asian immigrant women's patriarchal beliefs and found that almost 40 % of women had experienced IPV in the past 5 years which the authors state is three times higher than the Canadian general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation